Anti-ulcerative colitis effects of chemically characterized extracts from Calliandra haematocephala in acetic acid-induced ulcerative colitis - Rehman, Inaam Ur; Saleem, Mohammad; Raza, Syed Atif; Bashir, Saher; Muhammad, Taha; Asghar, Shahzad; Qamar, Muhammad Usman; Shah, Tawaf Ali; Bin Jardan, Yousef A.; Mekonnen, Amare Bitew; Bourhia, Mohammed (Frontiers in Chemistry, 2024)
Background: Ulcerative colitis is a chronic immune-mediated inflammatory bowel disease . To date, no definite cure for this disease is available.The objective of the current study was to assess the effect of Calliandra haematocephala on inflammatory mediators and oxidative stress markers for the exploration of its anti-ulcerative colitis activity in rat models of acetic acid-induced ulcerative colitis.Methods: Methanolic and n-hexane extracts of areal parts of the plant were prepared by cold extraction method. Phytochemical analysis of both extracts was performed by qualitative analysis, quantitative methods, and highperformance liquid chromatography (HPLC). Prednisone at 2 mg/kg dose and plant extracts at 250 mg/kg, 500 mg/kg, and 750 mg/kg doses were given to Wistar rats for 11 days, which were given acetic acid on 8th day through the trans-rectal route for the induction of ulcerative colitis. A comparison of treatment groups was done with a normal control group and a colitis control group. To evaluate the anti-ulcerative colitis activity of Calliandra haematocephala, different parameters such as colon macroscopic damage, ulcer index, oxidative stress markers, histopathological examination, and mRNA expression of pro and anti-inflammatory mediators were evaluated. mRNA expression analysis was carried out by reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR).The phytochemical evaluation revealed polyphenols, flavonoids, tannins, alkaloids, and sterols in both extracts of the plant. Results of the present study exhibited that both extracts attenuated the large bowel inflammation and prevented colon ulceration at all tested doses. Macroscopic damage and ulcer scoreswere significantly decreased by both extracts. Malondialdehyde (MDA) levels and nitrite/nitrate concentrations in colon tissues were returned to normal levels while superoxide dismutase (SOD) activity was significantly improved by all doses. Histopathological examination exhibited that both extracts prevented the inflammatory changes, cellular infiltration, and colon thickening. Gene expression analysis by RT-qPCR revealed the downregulation of pro-inflammatory markers such as tumor necrosis factor-alpha (TNF-α) and cyclooxygenase-2 (COX-2) whereas the anti-inflammatory cytokines including Interleukin-4 (IL-4) and Interleukin-10 (IL-10) were found to be up-regulated in treated rats.It was concluded based on study outcomes that methanolic and n-hexane extracts of Calliandra haematocephala anti-ulcerative colitis activity through modulation of antioxidant defense mechanisms and the immune system.